2012
DOI: 10.1016/j.jml.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The development of long-term lexical representations through Hebb repetition learning

Abstract: The Hebb repetition effect and naturalistic word-form learning AbstractThis study clarifies the involvement of short-and long-term memory in novel word-form learning, using the Hebb repetition paradigm. In Experiment 1, participants recalled sequences of visually presented syllables (e.g., la-va-bu-sa-fa-ra-re-si-di), with one particular (Hebb) sequence repeated on every third trial. Crucially, these Hebb sequences contained three orthographic nonword neighbours of existing Dutch base-words (e.g., lavabu -lava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
122
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(133 citation statements)
references
References 41 publications
11
122
0
Order By: Relevance
“…It extends the previous examination of HRL in adults with dyslexia (Szmalec et al, 2011) by including not only an initial Hebb-learning session with a much larger number of Hebb repetitions (up to 20 in the current study vs. 12 in Szmalec et al, 2012) but also relearning on the subsequent day and one month after initial learning. This allows us to Serial-order learning in dyslexia estimate the retention of the learned Hebb sequences over time.…”
Section: Current Studysupporting
confidence: 54%
See 4 more Smart Citations
“…It extends the previous examination of HRL in adults with dyslexia (Szmalec et al, 2011) by including not only an initial Hebb-learning session with a much larger number of Hebb repetitions (up to 20 in the current study vs. 12 in Szmalec et al, 2012) but also relearning on the subsequent day and one month after initial learning. This allows us to Serial-order learning in dyslexia estimate the retention of the learned Hebb sequences over time.…”
Section: Current Studysupporting
confidence: 54%
“…With this aim, participants again learned Hebb sequences (e.g., lava-bu-sa-fa-ra-re-si-di), containing lexical competitors (e.g., lavabu, safara, residi) of Inherent to the use of the lexical competition approach is the requirement that Hebb sequences closely resemble known words represented in the mental lexicon. Importantly, the earlier studies using this lexical-competitor approach (Szmalec et al, 2012) have demonstrated that this procedure yields Hebb learning curves (for normal readers) comparable to standard verbal Hebb learning curves (Szmalec et al, 2009(Szmalec et al, , 2011(Szmalec et al, , 2012, suggesting that the learning of syllable sequences derived from existing words does not seem to rely on strong support from these words. This might be due to the fact that the Hebb procedure exposes the participant to individual syllables, presented one by one, while the gradual and implicit grouping of those syllables into pseudoword-forms is only the outcome of the Hebb-learning process.…”
Section: Methodsmentioning
confidence: 76%
See 3 more Smart Citations